PENINGKATAN PEMAHAMAN KONSEPTUAL DAN KEMAMPUAN KONEKSI MATEMATIS SISWA SMP MELALUI PENDEKATAN KONSTRUKTIVISTIK - Mimin, Philipus; Sugiatno, Sugiatno; Hartoyo, Agung (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractConceptual understanding of mathematic and mathematical connections became an important focus in the curriculum of mathematics. The population in this research were all students of IX SMP N 10 Pontianak, and the sample of the research was class IX D which selected by sampling. The form of research used was pre-experimental design with one group pre test-post test design. This research desig was devided into three phases, namely preparation phase, implementation phase, and data processing phase. Data collection techniques which used were test and non-test, the data have been obtained were analyzed by descriptive qualitative and quantitative methods. Generally, students? conceptual understanding and mathematical connection ability by using constuctivist approach learning has improved. Students? mathematical conceptual understanding at the begining belongs to medium category which percentage of 68.04%. This, students? mathematical connection ability at the begining before using constructivist approach belongs to low cateogry which was only 28,81%.The learning process was implented well, which was accordance with the lesson plan, and the results fell into a very good category. Students? mathematical conceptual understanding after learning process was categorized high which the percentage score of 87,78%. Meanwhile, students? mathematical connection ability after learning was categorized as high as 77.14%.Keywords: mathematical conceptual, mathematical connection, constructivist,                  mathematical knowledge.